An Aqueous Rechargeable Fluoride Ion Battery with Dual Fluoride Electrodes. Issue 12 (1st January 2019) - Hou, Xianhua; Zhang, Zishuai; Shen, Kaixiang; Cheng, Shikun; He, Qinyu; Shi, Yumeng; Yu, Denis Y. W.; Su, Ching-yuan; Li, Lain-Jong; Chen, Fuming
Abstract : An anion flow battery has recently emerged as an option to store electricity with high volumetric energy densities. In particular, fluoride ions are attractive for these batteries because they have the smallest size among anions, which is beneficial for charge transport. To date, reported fluoride ion batteries either operate with an ionic liquid, organic electrolyte or solid-state electrolyte at high temperatures. Herein, an aqueous fluoride ion flow battery is proposed that consists of bismuth fluoride as the anode, 4-hydroxy-TEMPO (TEMPO) as the cathode, and NaF salt solution as the aqueous electrolyte. During the charging process, bismuth fluoride electrochemically releases fluoride ions with the formation of bismuth metal, while TEMPO captures the fluoride ions. A reversible and stable discharge capacity of 89.5 mAh g −1 was achieved at 1000 mA g −1 after 85 cycles. The fluoride ion battery possesses excellent rate performance. To the best of our knowledge, this is the earliest demonstration that fluoride ion batteries can work in aqueous solutions, which can be used for future clean energy applications.